2012
DOI: 10.1097/ico.0b013e318243e446
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sleep Apnea Syndrome and High-Risk Characteristics Among Keratoconus Patients

Abstract: Keratoconus patients are at increased risk for sleep apnea, and different risk factors are associated with sleep apnea in keratoconus patients and controls. Ophthalmologists should consider screening keratoconus patients for obstructive sleep apnea, if appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 40 publications
0
14
1
2
Order By: Relevance
“…As a consequence these children are either at risk or suffer from a host of health disorders, such as asthma, cancer, obesity and hyperactivity . Although we have not observed obesity among KC patients, there are reports in the literature of such an association . More research is needed to substantiate our finding.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…As a consequence these children are either at risk or suffer from a host of health disorders, such as asthma, cancer, obesity and hyperactivity . Although we have not observed obesity among KC patients, there are reports in the literature of such an association . More research is needed to substantiate our finding.…”
Section: Discussionmentioning
confidence: 52%
“…77 Although we have not observed obesity among KC patients, there are reports in the literature of such an association. [78][79][80] More research is needed to substantiate our finding.…”
Section: Discussionmentioning
confidence: 87%
“…One could speculate that the high prevalence of OSA in the studies conducted by Pihlblad and Schaefer,2 Gupta et al 3 and Saidel et al 4 in patients with KC could be secondary to the high prevalence of obesity and the higher mean age of their patients; the mean BMI of patients with KC in their studies was 32.4, 31.2 and 29.9, respectively 2–4. The mean age of patients in these studies was 47, 45 and 47 years, respectively 2–4.…”
Section: Discussionmentioning
confidence: 91%
“…In a series of 50 patients, Pihlblad and Schaefer2 found that the prevalence of obstructive sleep apnoea (OSA) in the patients with KC was 24%. However, in similar studies, Gupta et al 3 and Saidel et al 4 found the frequency of OSA among patients with KC to be 18% and 19.6%, respectively.…”
Section: Introductionmentioning
confidence: 84%
“…10,11,19,20 Bizim hastalarımızın keratometri değerleri normal sınırlar içe-risinde idi ve hiçbirinde keratokonus yoktu. Çalışmamızda keratokonuslu hasta saptanmaması-nın nedeni değerlendirilen OUAS hasta sayısının az olması olabilir.…”
Section: İstati̇sti̇ksel Anali̇zunclassified